1991
DOI: 10.4269/ajtmh.1991.44.314
|View full text |Cite
|
Sign up to set email alerts
|

An Immunogenetically Defined and Immunodominant Trypanosoma Cruzi Antigen

Abstract: Two strains of mice, A. SW (H-2') and A.CA (H-7), were immunized with live trypomastigotes or epimastigotes of the Tulahuen strain of Trypanosoma cruzi or with their sonicates. By immunowestern blotting, sera from A.SW mice, but not from A.CA, recognized, in an immunodominant fashion, a 45 kDal polypeptide (Tc45) present in both epimastigotes and trypomastigotes. Since A.SW and A.CA strains are congenic for the major histocompatibifity H-2 complex, recognition of Tc45 seems to be controlled by this genetic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In contrast, we have shown that epimastigotes display an important amount of TcCRT in the cytoplasmic compartment (45). Although the presence of TcCRT in supernatants from trypomastigote and epimastigote cultures, on the epimastigote surface, and in sera of T. cruzi-infected individuals and mice, should be addressed, at present it is not possible to estimate the real TcCRT concentrations in the relevant parasite in vivo microenvironment.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In contrast, we have shown that epimastigotes display an important amount of TcCRT in the cytoplasmic compartment (45). Although the presence of TcCRT in supernatants from trypomastigote and epimastigote cultures, on the epimastigote surface, and in sera of T. cruzi-infected individuals and mice, should be addressed, at present it is not possible to estimate the real TcCRT concentrations in the relevant parasite in vivo microenvironment.…”
Section: Discussionmentioning
confidence: 81%
“…Native TcCRT is immunogenic in humans (43,44) and mice (45). Thus, most, if not all, T. cruzi-seropositive humans display variable amounts of anti-TcCRT Igs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, when ␤ 2 -microglobulin binds to the major histocompatibility complex (MHC) class I ␣ chain, the partially folded ␣␤ 2 -microglobulin heterodimer dissociates from calnexin and binds calreticulin. [14][15][16] The findings previously reported by this laboratory, 7,17,18 have characterized the immunogenicity and diagnostic value of T. cruzi calreticulin, then known as Tc45. These results plus those reported here open a wide range of possibilities to study the role of this immunologically relevant molecule in parasite infectivity and its potential immunoprophylactic and immunodiagnostic value.…”
Section: Introductionmentioning
confidence: 96%